Cardiovascular risk factors and impending 10-year risk of fatal or non-fatal cardiovascular disease events among an urban population in Tamil Nadu state in South India - A community based cross-sectional study - Uma Priyadharsini Thulasimani; Ponnusamy, Kalidas; Devarasu, Usha; Kolandasamy, Kokila; Paramasivam Mahendran, Siva (Asian Journal of Medical Sciences, 2023)
Background: Coronary heart disease, peripheral arterial disease, cerebrovascular disease, congenital and rheumatic heart illnesses are among the heart and blood vessel disorders classified as cardiovascular diseases (CVDs). Sudden premature cardiovascular deaths among apparently healthy population can be well prevented by the early recognition of cardiovascular risk factors using validated cardiovascular risk prediction tools. Aims and Objectives: The World Health Organization/international society of hypertension (WHO/ISH) Risk Prediction Charts was utilized to estimate the upcoming 10-year risk of CVD events, and the study’s objectives were to identify the risk factors for high CVD risk among urban residents aged ≥40–79 years in Tamil Nadu State, South India. Materials and Methods: A total of 350 participants were selected for a community-based cross-sectional study using a two-stage selection technique. A pretested questionnaire, anthropometry and laboratory research were used to acquire the required data. Finding the relationship between the risk factors and high CVD risk among the subjects was done using both univariate and multivariate regression analysis. Results: Mean age of subjects was 55.6 years. Hypertensives and diabetics were 35.4% and 27.4%, respectively. An alarming 75.1% subjects were either overweight or obese. The WHO/ISH chart categorized 20.9% subjects with >10% risk of impending CVDs. Risk factors which independently influenced high cardiovascular risk were “being unmarried” (adjusted odds ratio [aOR] 31.76; 95% CI; P=0.009), “positive family history” (aOR 4.13; P=0.017), “Sedentary Occupation” (aOR 3.18; P=0.036), and “alcohol usage” (aOR 3.03; 95% CI [1.06–10.27]; P=0.039). Conclusion: The study has identified that more than one-fifth of the subjects were under the >10% CVD risk category thereby underscoring the immediate need for inclusion of CVD risk scoring tools in routine screening programs in all levels of health care settings as an effective health promotion strategy in curtailing the escalating incidence of CVDs events worldwide.